1999
DOI: 10.1090/s0002-9939-99-05097-2
|View full text |Cite
|
Sign up to set email alerts
|

Residually finite, congruence meet-semidistributive varieties of finite type have a finite residual bound

Abstract: Abstract. We show that a residually finite, congruence meet-semidistributive variety of finite type is residually < N for some finite N . This solves Pixley's problem and a special case of the restricted Quackenbush problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…This condition is, for example, equivalent to congruence neutrality ( [19], [20]), or to having no covers of types 1 or 2 in congruence lattices of finite algebras in the variety (holds for locally finite varieties, [5]). It also implies the truth of Park's Conjecture, [12] (as proved by Ross Willard in [15]), and also Quackenbush's Conjecture , [13] (which holds trivially in congruence distributive case due to Jónsson's Lemma, [6], and is proved for the congruence meet-semidistributive case by Kearnes and Willard in [8]). Recently, the research in the Constraint Satisfaction Problem has shown that congruence meet-semidistributivity of the variety generated by the algebra of compatible operations is equivalent to the condition that the particular algorithm called 'localconsistency checking' would faithfully solve the Constraint Satisfaction Problem.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…This condition is, for example, equivalent to congruence neutrality ( [19], [20]), or to having no covers of types 1 or 2 in congruence lattices of finite algebras in the variety (holds for locally finite varieties, [5]). It also implies the truth of Park's Conjecture, [12] (as proved by Ross Willard in [15]), and also Quackenbush's Conjecture , [13] (which holds trivially in congruence distributive case due to Jónsson's Lemma, [6], and is proved for the congruence meet-semidistributive case by Kearnes and Willard in [8]). Recently, the research in the Constraint Satisfaction Problem has shown that congruence meet-semidistributivity of the variety generated by the algebra of compatible operations is equivalent to the condition that the particular algorithm called 'localconsistency checking' would faithfully solve the Constraint Satisfaction Problem.…”
Section: Introductionmentioning
confidence: 74%
“…//the same procedure for digraphs with four two-element subalgebras // the backtracking is shortened for 8 members here // there are 15 iterations in this case // we change the limit in g_wnu3, g_3 and back_3 from 10 to 8 as explained above // for each iteration we redefine functions // set_arr8, check8 and n8_arr2 //like explained above, // that is depending on the subalgebras present set_arr8(); num3=0; num =0; num2=0; num4=0; for(i=0 /* this keeps all the permutations except for the identity one*/ perm[0] = "0132"; perm [1] = "0213"; perm [2] = "0231"; perm [3] = "0312"; perm [4] = "0321"; perm [5] = "1023"; perm [6] = "1032"; perm [7] = "1203"; perm [8] = "1230"; perm [9] = "1302"; perm [10] = "1320"; perm [11] = "2013"; perm [12] = "2031"; perm [13] = "2103"; perm [14] = "2130"; perm [15] = "2301"; perm [16] = "2310"; perm [17] = "3012"; perm [18] = "3021"; perm [19] = "3102"; perm [20] = "3120"; perm[21] = "3201"; perm[22] = "3210"; for( i=0; i<23; i++) { for(j=0; j <16; j++) aux[j] ='0'; aux [16]…”
Section: The Conjecturementioning
confidence: 99%
See 3 more Smart Citations